Hitherto unknown eight-connected frameworks formed from A4B4O12 metal organophosphate heterocubanes. Issue 55 (21st June 2019) - Sharma, Kamna; Gupta, Sandeep K.; Borah, Aditya; Murugavel, Ramaswamy
Abstract : Hierarchy, on one's own volition! Transformation of 0-D clusters into 8-connected 3D-frameworks is an art by itself. The present work showcases how this can be achieved starting from a Zn4 P4 O12 heterocubanes decorated with –NH2 functionalities. Abstract : Modulation of a functional group on the distal part of a phosphate ester has been prudently exploited to selectively switch between the formation of D4R SBUs and 3-D framework structures. While amino substitution at the para -position of an aryl phosphate results in the isolation of tetra-amino functionalized discrete D4R zinc phosphate or its 4-connected 3-D framework, the introduction of an acetylamino substituent leads to a single-step assembly of a rare eight-connected 3-D framework solid.